THE MORPHOLOGICAL APPROACH OF THE CAMBRIDGE PRIMARY ENGLISH CURRICULUM AND ITS POTENTIAL APPLICATION IN UZBEK LANGUAGE EDUCATION (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This article analyzes the core principles and methodological approaches to teaching morphology within the Cambridge Primary English curriculum. It demonstrates that morphology in this curriculum is not presented as a separate module, but is integrated into reading, writing, and communicative competencies through a principle of gradual progression. The article also examines key principles of the Cambridge approach – such as functional grammar, text-based instruction, and alignment with the CEFR – and discusses the possibilities of applying these principles to mother-tongue (Uzbek) language education. The study concludes that adapting the Cambridge model to local educational conditions can contribute to the development of a modern, scientifically grounded, and practice-oriented model of morphological minimum in Uzbekistan.